IMPLICATIONS OF DHARMAGITA LEARNING TOWARDS THE DEVELOPMENT OF STUDENTS' COMPETENCIES AT PASANTIAN WIRAMA SANTI SASMITA KAPAL VILLAGE MENGWI BADUNG - I Made Dharmawan; I Gusti Ngurah Sudiana; I Made Surada (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
Dharmagita are sacred songs that specifically contain dharma values and are used to accompany Hindu religious ceremonies. Badung is one of the regencies in Bali Province which is quite intense in developing community skills for Dharmagita, one of is through Pasantian Wirama Santi Sasmita. Regarding on that, researchers are interested in studying further the implications of Dharmagita learning for students at the Pasantian Wirama Santi Sasmita, Desa Adat Kapal, Mengwi District, Badung Regency, by studying in depth and specifically the implications of implementing Dharmagita at Pasantian Wirama Santi Sasmita on the development of student competencies both in the realm of spiritual and social attitudes (affective), knowledge (cognitive), and also skills (psychomotor). To solve the formulation of the problem, the type of research used in this research was descriptive qualitative research, with a phenomenological approach. The results of this study indicated that the implications of implementing Dharmagita at Pasantian Wirama Santi Sasmita consist of implications for participants which describe strengthening spiritual attitudes, developing social attitudes, increasing knowledge, and developing skills (psychomotor).